Knowledge affects in epistemology: choice and subjectivity in Communication research - Martino, Luis Mauro Sa; Marques, Angela Cristina Salgueiro (MATRIZes, 2018)
This essay outlines some aspects of subjectivity and otherness in Communication Research. It argues that, in Communication Research, subjectivity is the prime research condition, and the relationship with the otherness preceds any epistemological action. Historically, from a Positivist point of view, subjectivity is an obstacle for scientific research, as it would be the place for affects and emotions that disturbs the rational evaluation of anything. However, distinguished epistemologists such as Bachelard and Morin have argued that subjectivity is a condition of scientific knowledge, as there is no ‘objective’ knowledge outside the conditions of knowing.